PENERAPAN MODEL PEMBELAJARAN KOOPERATIFTIPE TWO STAY TWO STRAY ( TSTS ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 016 SEKELADI ROKAN HILIR - Dasrul '; Mahmud '; Drs. Lazim. N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstact: The research aims to find out whether the implementation of two stay two stray (TSTS) method can improve social sciense learning results of class V student in SD Negeri 016 Sekeladi. The type of this research is classroom action research (CAR) with the research subjects are class V students which amounts to 24 students. The data collection techniques used is observation and tests. The research concluded that social sciense learning which using two stay two stray (TSTS) method can improve the teacher’s activity, student’s activity and social science learning result. At the first meeting of cycle I, the teacher’s activity percentage was 56,26% and categorized enouhg, at the second meeting the percentage increased to be 75% and categorized good. For cycle II at the first meeting the percentage was 81,25% and categorized very good, at the second meeting increased to be 91,66% and categorized very good. Then for student’s activity cycle I at the first meeting the percentage was 72,91% and categorized good, in the second meeting the percentage was 89,58% and categorized very good. The student’s social science learning result from the average grades before action (basic score) was 60,75 increased at cycle I to be 69,79 with the percentage increase by 14,88% and at cycle II the average grades increased to be 73,54 with the percentage increase by 21,05% from the basic score by 60,75.Keywords: Cooperative Type TSTS, Learning Outcomes